EXTRACTION , PURIFICATION AND PARTIAL CHARACTERIZATION OF PHYTIC ACID FROM DEFATTED SESAME OIL CAKE - & Shakir, Rasheed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
In this study phytic acid (PA) extracted from defatted sesame oil cake using three different solutions              (distilled water , HCl 0.5 M , TCA 3% ) , then it was purified by removing of protein and minerals, and tested for the prevention of  browning in apple slices and color degradation of anthocyanin solution during storage time at room temperature(25°C).  The antioxidant activities of irradiated and non- irradiated phytic acid were tested on DPPH radical. The results revealed that the highest phytic acid percentage was observed with TCA 3% after 6 hr extraction  with (2:100 w/v) solid: liquid ratio, and the lowest values were noticed with distilled water at all mixing ratios. It has been noticed that the purified PA was effective in preventing color degradation for anthocyanin solution when used at 0.025% and 0.05% over 11 days storage at room temperature, and it was also effective in preventing apple slice browning  when apple samples immersed for 10 min  in phytic acid solutions (0.5 % & 1.0 % ) and stored in polyethylene bags (vacuumed) at 7°C for 37 days. The antioxidant capacity of the purified phytic assay showed that the phytic acid irradiated at 22kGy gave the highest antioxidant activity whereas the non- irradiated phytic had  no antioxidant activity on DPPH radical.